Identification of Phytochemical Compounds, Extraction Yield, and Total Soluble of Red, Brown, and Green Seaweeds - Hasani Rahmawati; Dedin Finatsiyatul Rosida (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study examined the effects of seaweed species and solvent types on the yield and phytochemical profile of seaweed extracts obtained via Ultrasound–Microwave Assisted Extraction (UMAE). Five types of seaweed Eucheuma cottonii, Gelidium sp., Gracilaria sp., Sargassum sp., and Ulva lactuca were extracted using methanol and ethanol. Phytochemical screening was conducted for alkaloids, phenols, flavonoids, saponins, tannins, steroids, and terpenoids. The results showed that the extract yield ranged from 18.16% to 48.37%, with the highest yield of 48.37% observed in the methanol extract of E. cottonii. Total soluble solids ranged from 14.0% to 37.5%, with the highest value of 37.5% found in the methanol extract of E. cottonii. Phenolic compounds were detected in most extracts; flavonoids were present in all methanol extracts and some ethanol extracts; saponins were found in E. cottonii, Gracilaria sp., Sargassum sp., and Ulva lactuca; steroids were present in the ethanol extracts of Gracilaria sp. and Sargassum sp.; and terpenoids were detected in E. cottonii, Gelidium sp., and U. lactuca. The results indicate that the type of solvent affects the yield, total dissolved solids, and phytochemical profile of the extracts; thus, the Ultrasound–Microwave Assisted Extraction (UMAE) method has the potential to be an effective green extraction method for various types of seaweed. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption And ProductionSDG 14: Life Below Water